Dr. C.F. Shah and his innovations - Dixit, Mukund R., (SAGE knowledge. Cases., 2016)
This case describes the innovations of a medical practitioner over six decades of practice. It provides an opportunity to the participants to analyse the motivation, processes, constraints and outcomes or innovating efforts of individuals as opposed to corporates.